KEMAMPUAN MENULIS CERITA FABEL MENGGUNAKAN MODEL EXAMPLES NON-EXAMPLES SISWA KELAS VII D SMP NEGERI 6 MUARO JAMBI TAHUN AJARAN 2017/2018 - Ika Putri Sari; Abdoel Gafar; Firman Tara (Universitas Batanghari, 2019)
The aim of this research is to describe the students ability in writing fable by using examples non examples model at class VII D SMP Negeri 6 Muaro Jambi Academic Year 2017/2018. This research used quantitative correlation approach. The population of the research was class VII D SMP Negeri 6 Muaro jambi. The sample of the research consisted of one class, 12 men and 18 women with total sample was 30 people. The data was collected by using pre-test by using conventional method and post-test by using examples non examples model. The result of the research shows that the value of tcount is 7.766. Meanwhile the value of ttable is required from table t with dk 28 and the siginicance () is 0,05. By comparing the value of tcount and ttable it is required tcount > ttable, it means Ho is rejected and Ha is accepted. Thus, it can be concluded that the use of examples non examples model can be used in increasing the ability of the students in writing fable at class VII D SMP Negeri 6 Muaro Jambi with the mean score of post-test is 82.63 higher that the mean of pre-test 70.20. Keywords: writing, fable, model examples non examples